Cardiac arrest in a mother and daughter and the identification of a novel RYR2 variant, predisposing to low penetrant catecholaminergic polymorphic ventricular tachycardia in a four‐generation Canadian family. Issue 4 (28th January 2020) - Tung, Matthew; Van Petegem, Filip; Lauson, Samantha; Collier, Ashley; Hodgkinson, Kathy; Fernandez, Bridget; Connors, Sean; Leather, Rick; Sanatani, Shubhayan; Arbour, Laura
Abstract: Background: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a rare inherited arrhythmia syndrome characterized by adrenergically driven ventricular arrhythmia predominantly caused by pathogenic variants in the cardiac ryanodine receptor (RyR2). We describe a novel variant associated with cardiac arrest in a mother and daughter. Methods: Initial sequencing of the RYR2 gene identified a novel variant (c.527G > T, p.R176L) in the index case (the mother), and her daughter. Structural analysis demonstrated the variant was located within the N‐terminal domain of RyR2, likely leading to a gain‐of‐function effect facilitating enhanced calcium ion release. Four generation cascade genetic and clinical screening was carried out. Results: Thirty‐eight p.R176L variant carriers were identified of 94 family members with genetic testing, and 108 family members had clinical evaluations. Twelve carriers were symptomatic with previous syncope and 2 additional survivors of cardiac arrest were identified. Thirty‐two had clinical features suggestive of CPVT. Of 52 noncarriers, 11 had experienced previous syncope with none exhibiting any clinical features of CPVT. A documented arrhythmic event rate of 2.89/1000 person‐years across all carriers was calculated. Conclusion: The substantial variability in phenotype and the lower than previously reported penetrance is illustrative of the importance of exploring family variants beyond first‐degree relatives. Abstract : Here, we present a family study and structural analysis of a likely pathogenic RYR2 variant causing CPVT in a four‐generation Canadian family. If considering only the first‐degree relatives of our index case, the phenotype would seem to be highly penetrant and considered "severe." However, with expanded, four‐generation genetic testing and clinical assessments (including 38 carriers of the variant) we show that the overall penetrance of the variant is low, illustrating the importance of exploring family variants beyond first‐degree relatives.